Using Modified Bessel Functions for Analysis of Nonlinear Effects in a MOS Transistor Operating in Moderate Inversion - Filanovsky, Igor M. (2020)
This work was supported in part by the NSERC, Canada, in part by the Portuguese Foundation for Science and Technology under Project PESTOEEEI/UI0066/2015 and foRESTER Project PCIF/SSI/0102/2017, and in part by the Academy of Finland.